Manufacturing method of iron-based soft magnetic alloy

Through single-roll cooling method and alloy composition optimization, iron-based flexible magnetic alloy sheets were prepared, which solved the problems of low Bs and high iron loss in the prior art, and achieved the performance of Bs≧1.7T and low iron loss, and was suitable for high-frequency electromagnetic components and motor cores.

JP7656988B1Active Publication Date: 2025-04-04NEXT CORE TECHNOLOGIES CO LTD

Patent Information

Application Number
JP2024162037
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-04-04
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

It is difficult to produce iron-based flexible magnetic alloy powder in the prior art, achieving high saturation flux density and low iron loss of Bs≧1.7T, and is suitable for electromagnetic components and motor cores in high frequency bands.

Method used

The iron-based flexible magnetic alloy sheet was prepared by single-roll cooling method. By adjusting the alloy composition (Fe; 1-m Com) 100-x-y Si x (B) 1-n C n) y) and processing parameters (such as the rotation speed and surface roughness of the cooling-roll), the α-Fe phase in the alloy is the main phase, the Bs is between 1.7 T and 2.0 T, and the powder is prepared by grinding.

Benefits of technology

The high saturation flux density and low iron loss performance of iron-based flexible magnetic alloy powder are achieved, and are suitable for electromagnetic components and motor cores in high frequency bands, reducing electrical energy consumption and heat generation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007656988000001_ABST
    Figure 0007656988000001_ABST
Patent Text Reader

Abstract

The present invention provides a method for producing an iron-based soft magnetic alloy having Bs≧1.7T and low core loss performance, which is suitable as a dust core material. [Solution] Composition formula (Fe 1-m Co m ) 100-x-y S x (B 1-n C n ) y and the composition ratios x, y, m and n satisfy 0.5≦x≦1.5 atomic %, 11.0≦y≦13.0 atomic %, 0.05≦m≦0.5 and 0.0≦n≦0.3, respectively; and a rapid solidification step of rapidly solidifying the molten alloy on a cooling roll whose main raw material is any one of pure copper, a copper alloy, Mo and W.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing an iron-based soft magnetic alloy, and more particularly to a method for producing an iron-based soft magnetic alloy suitable as a material for dust cores. [Background technology]

[0002] In recent years, the market has been demanding materials with low iron loss and high saturation magnetic flux density for various passive elements and transformers in the power electronics field, such as inductors and reactors used as electronic components. In addition to Fe-Si-B iron-based amorphous alloy powder, a soft magnetic powder with excellent DC superposition characteristics and low iron loss is known. Fe-Si-B-Nb-Cu iron-based nanocrystalline alloy powder is obtained by crushing an Fe-Si-B amorphous alloy ribbon with a thickness of about 17 μm to 25 μm, which is produced by quenching and solidifying a melt made mainly of iron (Fe), silicon (Si), and boron (B), after appropriate crystallization heat treatment. There is an increasing market demand for this powder for dust cores (compressed powder magnetic cores) to replace Fe-Si alloy powder produced by the conventional atomization method or Fe-Si-B-Cr amorphous powder produced by the SWAP method, for inductors, reactors, power conditioners, motor cores, etc.

[0003] In addition, the Fe-Si-B amorphous alloy powder and Fe-Si-B-Nb-Cu iron-based nanocrystalline alloy powder are being considered as core materials for power electronics used in the several kHz to MHz (megahertz) band, taking advantage of their low iron loss compared to Fe-Si alloy powder. It has been confirmed that these alloy powders can suppress the iron loss generated in the core, especially in high frequency bands exceeding 1 MHz, and achieve unprecedented high efficiency. Furthermore, in the current situation where about 60% of the world's electricity is consumed by motors, using dust cores in the stator cores of motors reduces not only iron loss but also eddy current loss, which can greatly contribute to high motor efficiency except for the issue that dust cores have a low magnetic flux density Bs. Therefore, as a direct means of realizing carbon-free, it is expected that they will be used in white goods such as electric vehicles and air conditioners, as well as motors for factory automation.

[0004] However, the above-mentioned Fe-Si-B amorphous alloy has a Bs ≦ 1.6 T, and the Fe-Si-B-Nb-Cu iron-based nanocrystalline alloy has a Bs ≦ 1.3 T, which is lower than the Bs ≧ 1.8 T of the Fe-Si alloy, which is the existing core material. Therefore, when used as a dust core, the Bs drops further. Therefore, as a dust core, it has not been widely used as an alternative material to Fe-Si alloy powder or pure iron powder, including for motor cores. There is a demand for an iron-based soft magnetic powder for dust cores that can achieve low iron loss performance comparable to Fe-Si-B amorphous alloy powder while maintaining high Bs performance comparable to Fe-Si alloy powder, which can be used for everything from passive elements for power electronics to motor cores.

[0005] Due to the above market demands, it is difficult for Fe-Si-B amorphous alloys, which have a maximum Bs of about 1.6 T, or iron-based nanocrystalline materials (e.g., FINEMET (registered trademark)), which have a Bs of about 1.4 T or less, to replace Fe-Si alloys with a Bs of 1.8 T. To date, there have been no examples of high Bs, low iron loss iron-based soft magnetic powders for dust cores that are capable of achieving low iron loss performance on a par with Fe-Si-B amorphous alloy powders.

[0006] For example, as mentioned above, core materials for power electronics used in the megahertz band and core materials for EV main motors, which require high-speed rotation of over 20,000 rpm, are dust cores made of pure iron or Fe-Si atomized powder, which have high iron loss. The iron loss generated in the core due to the input power causes heat to be generated in the entire passive element board or the motor, which not only increases power consumption but also requires electricity for cooling measures. Therefore, there is an extremely high market demand for high-Bs, low-iron-loss iron-based soft magnetic powder for dust cores that enables high output and high efficiency that can contribute to energy savings in a variety of applications.

[0007] Furthermore, if it is possible to significantly reduce the iron loss to less than one-tenth of that of iron-based amorphous alloys while maintaining a high Bs, it is expected that the powder will be used in a variety of fields as a dust core. For this reason, there are extremely high expectations from the market for an iron-based soft magnetic alloy powder for dust cores that achieves low iron loss comparable to that of iron-based amorphous alloys, with Bs≧1.7T obtained before crushing, by crushing a rapidly solidified alloy obtained by the single-roll quenching method, as an alternative to Fe-Si atomized powder, which has poor manufacturing yield and low recyclability.

[0008] In addition, both the Fe-Si powder obtained by the gas atomization method and the Fe-Si-B-Cr amorphous powder obtained by the SWAP method are spherical powders, and it is difficult to create a powder particle size distribution with a two-peak particle size distribution that allows for close packing, and the powder filling rate in the dust core is 70 to 80 volume% in compression molding and 50 to 70 volume% in injection molding. For this reason, in the iron-based soft magnetic powder produced by pulverizing the rapidly solidified alloy obtained by the single roll quenching method, a magnetic powder particle size distribution with a magnetic powder filling rate in the dust core of 80 volume% or more in compression molding and 70 volume% or more in injection molding is required to improve yield and achieve low cost.

[0009] In Non-Patent Document 1, it is stated that Fe-Si-B amorphous alloys have been 4 ~10 6It has been disclosed that an amorphous structure can be obtained only when the rapidly solidified alloy ribbon has a thickness of about 17 to 22 μm and is rapidly solidified at an extremely fast rapid solidification rate of, for example, 100,000 sec., but that it is possible to obtain an iron-based amorphous alloy ribbon with a thickness of 50 μm or more by slowing down the rapid solidification rate by adding phosphorus (P). However, not only does the addition of P cause a decrease in the saturation magnetic flux density Bs, but in the case of P-added alloys, the P component volatilizes during alloy melting, causing significant contamination inside the furnace, and therefore there are still few examples of its application in the industrial field.

[0010] Non-Patent Document 2 discloses that the Fe-Si-B-P-Cu system iron-based nanocrystalline alloy "NANOMET (registered trademark)" is a soft magnetic material with a high saturation magnetic flux density Bs: 1.85T and low iron loss performance comparable to that of an iron-based amorphous alloy. However, as with Non-Patent Document 1, the iron-based nanocrystalline alloy is a P-added alloy, and in addition to the fact that the P component volatilizes during alloy melting, causing significant contamination inside the furnace, it requires crystallization treatment by rapid heating heat treatment. Furthermore, since the thickness of the quenched alloy ribbon is thin and the shape of the powder after pulverization is flaky, the magnetic powder filling rate during dust core molding does not reach 80%, so the high Bs of 1.85T cannot be utilized, and there have been no examples of practical use as dust cores.

[0011] Non-Patent Document 3 discloses various soft magnetic properties of dust cores using Fe-Si-based atomized powder. The magnetic powder filling rate (relative density) of the dust core is 83% for Fe-3.5Si, whose iron loss is 10 times or more that of Fe-Si-B-based amorphous alloys, and 81% for Fe-6.5Si, whose iron loss is about 7 times that of Fe-Si-B-based amorphous alloys. These magnetic powder filling rate values ​​are higher than the magnetic powder filling rate of dust cores using general Fe-Si-based atomized powders, which is 80% or less, but the iron loss is significantly higher than that of Fe-Si-B-based amorphous alloys.

[0012] Non-Patent Document 4 discloses various soft magnetic properties of Fe-Cr-Si-B amorphous alloy powders produced by the SWAP method and dust cores using this powder. Fe-Cr-Si-B amorphous alloy powders feature low iron loss performance, just like Fe-Si-B amorphous alloys. However, in the SWAP method, the molten alloy is finely divided by gas atomization, and then sprayed into a high-speed rotating water flow to solidify, achieving a high molten metal quenching speed. In the process of obtaining an amorphous structure, a process of directly water-cooling the droplets is essential. For this reason, the addition of Cr is essential to ensure the oxidation resistance of the molten alloy, but since the addition of Cr reduces the Bs of the iron-based amorphous alloy, it is not possible to obtain an iron-based soft magnetic alloy powder for dust cores that ensures Bs≧1.7T and achieves low iron loss comparable to that of the iron-based amorphous alloy.

[0013] Patent Documents 1, 2, and 3 describe methods for producing rapidly solidified alloy ribbons with a thickness of 50 μm or more. However, none of them have produced an Fe-Si-B-based amorphous alloy with Bs ≧ 1.7 T, which is intended for use in laminated cores for BLDC motors for driving EVs. Furthermore, they have not produced an iron-based soft magnetic alloy powder for dust cores that has Bs ≧ 1.7 T before grinding and achieves low iron loss comparable to that of iron-based amorphous alloys.

[0014] Patent Document 4 discloses a method for producing a metal ribbon, characterized in that molten metal is ejected from a plurality of openings (multi-hole nozzles) arranged on a moving cooling substrate (rotating cooling roll) at a substantially right angle to the direction of movement of the substrate and each of which has an angle of 10 to 80° to the direction of movement, and then rapidly cooled and solidified. However, Patent Document 4 is an invention made for the purpose of reducing the variation in thickness of a metal ribbon in the width direction when producing a wide rapidly cooled ribbon. In addition, it is difficult to process a plurality of openings having an elongated parallelogram, trapezoid, or ellipse shape with angles of 10 to 80°, and there is also a problem of high nozzle processing costs, making it difficult to use on an industrial mass production level.

[0015] Patent Document 5 discloses a method for producing an Fe-Si-B amorphous alloy having a thickness of 40 μm or more, but does not disclose an alloy composition that can ensure Bs ≧ 1.7T. In addition, it does not aim to produce an iron-based soft magnetic alloy powder for dust cores that ensures Bs ≧ 1.7T before crushing and achieves low iron loss comparable to that of an iron-based amorphous alloy.

[0016] Patent Document 6 describes an Fe-Si-B based rapidly solidified alloy having a thickness of 40 μm to 70 μm and a saturation magnetic flux density Bs≧1.7T and a coercive force Hc≦200 A / m, and a method for producing the alloy. However, since 0.1 vol % to 10 vol % of an α-Fe phase precipitates in the surface layer during the rapid solidification process and the remainder of the rapidly solidified alloy is made of an amorphous structure, the pulverizability deteriorates, making it difficult to mass-produce an iron-based soft magnetic alloy powder for dust cores that ensures Bs≧1.7T and achieves low iron loss comparable to that of an iron-based amorphous alloy. [Prior art documents] [Patent documents]

[0017] [Patent Document 1] Patent Publication No. 5-329587 [Patent Document 2] JP 7-113151 [Patent Document 3] Patent Publication No. 8-124731 [Patent Document 4] Patent Publication No. 63-220950 [Patent Document 5] Patent Publication No. 2018-153828 [Patent Document 6] Patent Publication No. 2021-193199 [Non-patent literature]

[0018] [Non-Patent Document 1] Creation of new bulk metallic glass / amorphous thick plates with high saturation magnetic flux density (Tohoku University, Metallic Glass Research Center) Akihiro Makino, Ken Kubota, Tono Chuntao [Non-Patent Document 2] Latest research and development trends of ultra-low core loss, high iron content soft magnetic alloy "NANOMET", Journal of the Japan Society for Metals Material, Vol. 55, No. 3 (2016) [Non-Patent Document 3] Development of Fe-Si Powder for Powder Cores, Electric Steelmaking, Vol. 94, No. 1, 2023 [Non-Patent Document 4] Preparation of amorphous soft magnetic powder by a new water atomization method (SWAP method), "Powder and Powder Metallurgy" Vol. 48, No. 8, August 2001 Summary of the Invention [Problem to be solved by the invention]

[0019] If it were possible to significantly reduce the iron loss of Fe-Si atomized powder to less than 1 / 10 of that of iron-based amorphous alloys while still maintaining a high Bs, it could be used as a soft magnetic powder for dust cores that can be applied to inductors, reactors, power conditioners, and other core materials for power electronics, as well as motor cores, thereby contributing to reducing power consumption and saving energy in a variety of fields.However, it has been difficult to mass-produce iron-based soft magnetic alloy powder for dust cores that maintains Bs ≧ 1.7T, the same as Fe-Si alloys, in the rapidly solidified alloy state before grinding, and achieves low iron loss at the same level as iron-based amorphous alloys.

[0020] Therefore, the present invention aims to provide a method for manufacturing an iron-based soft magnetic alloy suitable as a material for dust cores by ensuring a Bs of 1.7T or more, which is comparable to that of Fe-Si alloys, in the rapidly solidified alloy state before pulverization, and by achieving low iron loss at the same level as that of iron-based amorphous alloys. [Means for solving the problem]

[0021] The method for producing an iron-based soft magnetic alloy according to the present invention comprises the steps of: 1-m Co m ) 100-x-y S x (B 1-n C n ) y where the composition ratios x, y, m, and n are expressed as follows:0.8 ≦x≦ 1.4 %, 11.0≦y≦13.0 atomic %, 0.05≦m≦0.5, and 0.0≦n≦0.3; and a rapid solidification step of rapidly solidifying the molten alloy on a chill roll made of any one of pure copper, copper alloy, Mo, and W as a main raw material, the chill roll being rotated at a roll surface speed of 20 m / sec or more 45 the molten alloy is sprayed from a nozzle onto the surface of the chill roll while rotating the roll at a speed of 10 m / sec or less to form a ribbon of rapidly solidified alloy having a thickness of 18 μm or more and less than 40 μm, the ribbon of rapidly solidified alloy having a metal structure mainly composed of α-Fe phase, a saturation magnetic flux density of 1.7 T or more and 2.0 T or less, and an iron loss of 15 W / kg or less at a magnetic flux density of 1.0 T and a frequency of 1 kHz, the surface roughness of the chill roll having an arithmetic mean roughness (Ra) of 0.01 μm or more and 0.6 μm or less, the nozzle being made of a material mainly composed of any one of quartz (SiO2), boron nitride (BN), silicon carbide (SiC), and alumina (Al2O3), and the molten alloy is sprayed at a pressure of 5 kPa or more and 50 kPa or less.

[0022] In this method for producing an iron-based soft magnetic alloy, the nozzle may be a single-slit nozzle, in which case it is preferable that the longitudinal direction of the slit is arranged perpendicular to the rotation direction of the chill roll, the opening width of the slit is 0.2 mm or more and 0.8 mm or less, and the distance from the nozzle to the chill roll is 0.1 mm or more and 2.0 mm or less.

[0023] Alternatively, the nozzle may be a strand nozzle having a plurality of holes arranged in a row perpendicular to the direction of rotation of the chill roll. In this case, it is preferable that the diameter of the holes is 0.6 mm or more and 1.3 mm or less, and the distance from the nozzle to the chill roll is 0.5 mm or more and 30.0 mm or less.

[0024] The ribbon-shaped rapidly solidified alloy preferably has a magnetic permeability of 2000 or more at a magnetic flux density of 1.0 T and a frequency of 1 kHz.

[0025] The method for producing the iron-based soft magnetic alloy preferably further comprises a crushing step of crushing the ribbon-shaped rapidly solidified alloy to an average powder particle size of 200 μm or less to form an iron-based soft magnetic alloy powder, and a heat treatment step of heat treating the iron-based soft magnetic alloy powder at a constant temperature of 180° C. or more and 450° C. or less.

[0026] The iron-based soft magnetic alloy powder has a tap density of 2 g / cm 3 More preferably, it is equal to or greater than this.

[0027] The iron-based soft magnetic alloy powder preferably has a residual magnetic flux density Bs of 1.5 T or more. Effect of the Invention

[0028] According to the present invention, a manufacturing method for an iron-based soft magnetic alloy suitable as a material for dust cores can be provided by ensuring Bs≧1.7T, which is comparable to that of Fe-Si alloys, in the rapidly solidified alloy state before pulverization, and by achieving low iron loss at the same level as that of iron-based amorphous alloys. [Brief description of the drawings]

[0029] [Figure 1] FIG. 1(a) is a schematic diagram of a manufacturing apparatus used in a method for manufacturing an iron-based soft magnetic alloy according to one embodiment of the present invention, FIG. 1(b) is an enlarged view of the main parts thereof, FIG. 1(c) is an enlarged view of the bottom of a slit nozzle, and FIG. 1(d) is an enlarged view of the bottom of a strand nozzle. [Diagram 2] 1 is a powder X-ray diffraction profile of the iron-based soft magnetic alloy obtained in Example 2. [Diagram 3] 1 is a powder X-ray diffraction profile of the iron-based soft magnetic alloy obtained in Example 7. [Figure 4] 3 shows the powder particle size distribution of the iron-based soft magnetic alloy powder obtained in Example 2. [Diagram 5]1 shows the powder particle size distribution of the iron-based soft magnetic alloy powder obtained in Example 7. [Figure 6] 4 is a magnetization curve of the iron-based soft magnetic alloy powder obtained in Example 2. [Figure 7] 1 shows a magnetization curve of the iron-based soft magnetic alloy powder obtained in Example 7. [Figure 8] 1 is a comparison of magnetization curves of the iron-based soft magnetic alloy powders obtained in Examples 7 and 9. [Figure 9] 1 shows an iron loss curve of the magnetic flux density and iron loss at 20 kHz in a toroidal ring-shaped dust core using the iron-based soft magnetic alloy powder obtained in Example 2. [Figure 10] 1 is an X-ray diffraction profile of the Fe—Si—B based amorphous rapidly solidified alloy obtained in Comparative Example 10. [Figure 11] 1 is a powder X-ray diffraction profile of the iron-based soft magnetic alloy obtained in Comparative Example 12. [Figure 12] 1 shows the powder particle size distribution of the Fe—Si—B amorphous rapidly solidified alloy powder obtained in Comparative Example 10. [Figure 13] 13 is a magnetization curve of the Fe—Si—B amorphous rapidly solidified alloy powder obtained in Comparative Example 10. [Figure 14] 1 shows the powder particle size distribution of the Fe—Si—B based amorphous rapidly solidified alloy powder obtained in Comparative Example 12. [Figure 15] 13 is a graph showing a relationship between magnetic flux density and core loss at 20 kHz in a toroidal ring-shaped dust core using the Fe-Si-B amorphous rapidly solidified alloy powder obtained in Comparative Example 10. [Figure 16] 3 is a TEM photograph of the iron-based soft magnetic alloy powder of Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] The inventors have discovered that in a pseudo-ternary composition region of the essential elements Fe+Co, Si, and B, where the compounding ratios of each element are 0.5 atomic % or more and 1.5 atomic % or less for Si, 11 atomic % or more and 13 atomic % or less for B, with 5% or more and 50% or less of the remaining Fe being replaced with Co, and where a portion of B is replaced with C up to an upper limit of 30%, a rapidly solidified alloy can be obtained which has low iron loss performance equal to or better than that of an Fe-Si-B amorphous alloy, and which has excellent crushability while maintaining a saturation magnetic flux density Bs before crushing of 1.7 T or more, which is comparable to that of an Fe-Si alloy, and has thus arrived at the present invention.

[0031] [Alloy composition] By using Fe as an essential element to account for the remaining content of the above elements, and by substituting a portion of Fe with Co, which is a ferromagnetic element like Fe, it is possible to ensure Bs≧1.7T before pulverization. However, if the substitution rate m of Co for Fe is less than 5%, a Fe-B phase with low magnetization precipitates together with α-Fe, so Bs≧1.7T cannot be ensured, and if the substitution rate m of Co for Fe exceeds 50%, Bs tends to decrease. For this reason, the substitution rate m of Co for Fe is limited to 5% or more and 50% or less. The substitution rate m is preferably 5% or more and 30% or less, and more preferably 5% or more and 20% or less from the viewpoint of cost-effectiveness.

[0032] In the iron-based soft magnetic alloy obtained by the present invention, Si is not only an essential element for obtaining a fine structure, but also plays an important role in expressing soft magnetic properties such as magnetic permeability. If the composition ratio x of Si is less than 0.5 atomic %, not only the magnetic permeability at an applied magnetic field of 10 A / m deteriorates to less than 2000, but also the core loss (core loss) at 1 kHz and 1.0 T exceeds 15 W / kg, so that the characteristics of the iron-based soft magnetic alloy of the present invention, that is, high magnetic permeability and low core loss, are reduced. If the composition ratio x of Si exceeds 1.5 atomic %, the amorphous generating ability of the rapidly solidified alloy increases and the crushability of the rapidly solidified alloy decreases, so that not only is it not possible to obtain an iron-based soft magnetic alloy powder with an average powder particle size of 10 μm or more and 200 μm or less in the crushing process, but also if the composition ratio x of Si is too large, the abundance ratio of Fe responsible for magnetization decreases, and Bs≧1.7T cannot be obtained. For this reason, the composition ratio x of Si is set to 0.5 atomic % or more and 1.5 atomic % or less. The composition ratio x of Si is preferably 0.8 atomic % or more and 1.4 atomic % or less, and more preferably 1.0 atomic % or more and 1.3 atomic % or less.

[0033] If the composition ratio y of B+C is less than 11.0 atomic %, the metal structure of the iron-based soft magnetic alloy obtained by rapid solidification becomes coarse, so that the low iron loss performance of 15 W / kg or less at a magnetic flux density of 1.0 T and a frequency of 1 kHz cannot be ensured. In addition, if the composition ratio y of B+C exceeds 13.0 atomic %, the amorphous generation ability of the rapidly solidified alloy increases and the crushability of the rapidly solidified alloy decreases, so that not only is it not possible to obtain an iron-based soft magnetic alloy powder with an average powder particle size of 10 μm to 200 μm in the crushing process, but also the abundance ratio of Fe, which is responsible for magnetization, decreases, so that the rapidly solidified alloy before crushing cannot obtain Bs≧1.7T. For this reason, the composition ratio y of B+C is 11.0 atomic % to 13.0 atomic %. The composition ratio y of B+C is preferably 11.5 atomic % to 13.0 atomic % and more preferably 12.0 atomic % to 13.0 atomic %.

[0034] By replacing a portion of B with C, the melting point of the molten alloy is lowered, the rapid solidification conditions are relaxed, and the iron-based soft magnetic alloy of the present invention is easier to produce, but if the substitution rate n of C for B exceeds 30%, it is not preferable because it is not possible to ensure Bs≧1.7T of the rapidly solidified alloy before pulverization. For this reason, the substitution rate n is limited to 30% or less. From the viewpoint of achieving both high Bs characteristics and low magnetic permeability, the substitution rate n is preferably 20% or less, and more preferably 15% or less.

[0035] In the iron-based soft magnetic alloy obtained by the present invention, it is possible to add one or more additive elements selected from the group consisting of Al, Si, V, Ti, Mn, Zn, Ga, Zr, Nb, Mo, Ag, Hf, Ta, W, Pt, Au and Pb, but if the added concentration exceeds 2.0 atomic %, it is not preferable because the rapidly solidified alloy before pulverization cannot achieve Bs≧1.7T, and it is acceptable if it is mixed in as an impurity within 2.0 atomic %. Note that Cu is not solid-soluble in Fe, which is the main raw material, and if Cu is added, Cu dispersed in the ultrafine α-Fe structure will precipitate alone, which may hinder the formation of the desired alloy powder, so the iron-based soft magnetic alloy of the present invention does not contain Cu.

[0036] [Metal structure] The iron-based soft magnetic alloy obtained by the present invention is characterized by having an α-Fe phase as the main phase, which is isotropically precipitated without being oriented in a specific direction. The main phase is the phase with the largest volume ratio, and preferably has a volume ratio of 50% or more, and more preferably has a volume ratio of 80% or more. The isotropically precipitated α-Fe phase has a fine crystal structure with an average crystal grain size of less than 100 nm, and there are also ultrafine crystal structures that can be said to be crystal precursors with a crystal size of less than 1 nm. The crystal size of the α-Fe phase can be roughly determined from the half-width of the X-ray diffraction peak by powder X-ray diffraction (XRD), or can be obtained by observing the metal structure of the iron-based rapidly solidified alloy by a transmission electron microscope (TEM).

[0037] However, when the molten alloy is rapidly solidified on a rotating cooling roll, even if an amorphous phase and a small amount of Fe-B phase are mixed in the metal structure of the obtained iron-based soft magnetic alloy, it is acceptable as long as the amount does not adversely affect the soft magnetic properties. If the amorphous phase in the metal structure of the iron-based soft magnetic alloy powder exceeds 20 volume % of the entire metal structure, it becomes difficult to obtain Bs ≧ 1.7T, so the content ratio of the amorphous phase is 20 volume % or less. The content ratio of the amorphous phase is preferably 10 volume % or less, and more preferably 5.0 volume % or less.

[0038] When the iron-based soft magnetic alloy obtained by the present invention is pulverized and used in mass production as dust cores, if a coarse α-Fe crystal phase with an average crystal grain size of 100 nm or more oriented in the (200) direction (in-plane orientation) precipitated by non-uniform nucleation during the quenching and solidification process in the manufacture of the iron-based soft magnetic alloy is present near the surface of the quenching roll or free surface, it may be difficult to obtain the desired low iron loss performance. In order to obtain low iron loss performance of 15 W / kg or less at a magnetic flux density of 1.0 T and a frequency of 1 kHz, the α-Fe crystal phase precipitated in the surface layer of the iron-based soft magnetic alloy is preferably 10% by volume or less, and from the viewpoint of stably maintaining low iron loss performance, it is preferably 5.0% by volume or less, and more preferably 2.0% by volume or less. In the present invention, the surface layer refers to a depth from the surface of the iron-based soft magnetic alloy that is 10% of the thickness of the iron-based soft magnetic alloy.

[0039] [Magnetic properties] The iron-based soft magnetic alloy powder obtained by the present invention is characterized by a saturation magnetic flux density Bs of 1.7 T or more before pulverization, but if Bs exceeds 2.0 T, the core loss at a magnetic flux density of 1.5 T and a frequency of 1 kHz exceeds 50 W / kg, so no clear improvement in efficiency is obtained compared to dust cores using Fe-Si atomized powder. In order to obtain stable energy-saving performance from the commercial frequency band of 60 Hz to the megahertz band, the Bs of the rapidly solidified alloy before pulverization must be 1.7 T or more and 2.0 T or less, preferably 1.73 T or more and 1.97 T, and more preferably 1.75 T or more and 1.95 T or less.

[0040] When the iron-based soft magnetic alloy powder obtained by the present invention is used to manufacture a dust core having high Bs and low iron loss performance, it is effective that the powder has a Bs of 1.5 T or more when pulverized to an average powder particle size of 200 μm or less. The Bs of the iron-based soft magnetic alloy powder is preferably 1.55 T or more, and more preferably 1.6 T or more.

[0041] In addition, while the iron loss value at each operating frequency of existing Fe-Si atomized powder, iron-based amorphous alloy powder, and iron-based nanocrystalline alloy powder shows a tendency to increase with increasing magnetic flux density, the iron-based soft magnetic alloy obtained by the present invention shows a very unique magnetic property in that the iron loss value at each operating frequency shows a clear tendency to saturate with increasing magnetic flux density. In particular, the iron loss value at a magnetic flux density of 1.5 T at a frequency of 20 kHz, which is a high frequency range, is 1500 W / kg or less, and there is a possibility that the iron loss that is a problem in reactors and ultra-high speed rotating motors operating in the range of several tens of kHz to several tens of MHz can be significantly reduced. If the iron loss value at a frequency of 20 kHz and a magnetic flux density of 1.5 T is too high (e.g., 2000 W / kg or more), the iron loss will be at the same level as that of an iron-based amorphous alloy and an iron-based nanocrystalline alloy. Therefore, the iron loss value at a frequency of 20 kHz and a magnetic flux density of 1.5 T is preferably 1500 W / kg or less, more preferably 1300 W / kg or less, and even more preferably 1000 W / kg or less.

[0042] [Method of manufacturing iron-based crystalline alloy] The method for producing an iron-based soft magnetic alloy of the present invention includes a step of preparing a molten alloy having the above-mentioned composition, and a step of rapidly solidifying the prepared molten alloy. The method also includes a step of pulverizing the obtained iron-based soft magnetic alloy, thereby forming an iron-based soft magnetic alloy powder.

[0043] Fig. 1(a) is a schematic diagram of a single-roll molten metal quenching apparatus used in a method for producing an iron-based soft magnetic alloy according to one embodiment of the present invention, Fig. 1(b) is an enlarged view of a nozzle, and Fig. 1(c) is an enlarged view of the nozzle bottom. The single-roll molten metal quenching apparatus 1 shown in Figs. 1(a) to 1(c) includes a melting furnace 2, a molten metal storage vessel 5, and a cooling roll 8.

[0044] The melting furnace 2 supplies molten alloy 3, obtained by melting raw materials by high-frequency induction heating, to a molten metal storage container 5 by rotating a tilting shaft 4. The molten metal storage container 5 is equipped with a nozzle 6 at its bottom, and the molten alloy 3 is further heated by a heating coil (not shown) and ejected from a slit 7 formed at the lower end of the nozzle 6 onto the surface (outer circumferential surface) of a chill roll 8. Cooling water is supplied to the inside of the chill roll 8 to rapidly cool the molten alloy that comes into contact with the surface, forming a ribbon-like rapidly solidified alloy 9. The nozzle 6 is made of a material such as quartz (SiO 2 ), boron nitride (BN), silicon carbide (SiC) and alumina (Al 2 O 3 ) can be appropriately selected as the main component.

[0045] The nozzle 6 is a single slit nozzle in which a single slit 7 is formed, and the longitudinal direction of the slit 7 is arranged so as to be perpendicular to the rotation direction of the chill roll 8 (i.e., parallel to the rotation axis of the chill roll 8). The width W1 of the slit 7 plays a role in adjusting the rate of discharge of the molten alloy 3 supplied to the chill roll 8. If the slit width W1 is too small, slit processing is likely to become difficult, and furthermore, the slit 7 is likely to be blocked by the molten alloy. On the other hand, if the slit width W1 is too large, the discharge rate becomes too high, and the heat removal by the chill roll 8 is not kept up, and the rapidly solidified alloy sticks to the chill roll 8, making it difficult to continue stable molten rapid solidification. Therefore, the slit width W1 is 0.2 mm or more and 0.8 mm or less. The slit width W1 is preferably 0.3 mm or more and 0.7 mm or less, and more preferably 0.3 mm or more and 0.6 mm or less.

[0046] The nozzle 6 may be a strand nozzle shown in FIG. 1(d) instead of the slit nozzle shown in FIG. 1(c). In the strand nozzle shown in FIG. 1(d), a plurality of holes 7a are arranged in a row perpendicular to the rotation direction of the chill roll 8 (i.e., parallel to the rotation axis of the chill roll 8). The diameter of each hole 7a of the strand nozzle is 0.6 mm or more and 1.3 mm or less, preferably 0.7 mm or more and 1.2 mm or less, and more preferably 0.7 mm or more and 1.1 mm or less. If the diameter of the hole 7a is less than 0.6 mm, the amount of molten metal discharged per hole is small, so that the temperature at the tip of the nozzle 6 decreases, and there is a risk that the molten metal cannot be continuously discharged. On the other hand, if the diameter of the hole 7a exceeds 1.3 mm, the amount of molten metal discharged per hole becomes too large, so that the molten metal is not rapidly cooled completely, and coarse α-Fe, which causes a deterioration in magnetic properties, may be precipitated. Moreover, if the interval between the holes 7a is too small, the molten metal coming out of each hole 7a may come into contact with each other, leading to incomplete quenching of the molten metal and the precipitation of coarse α-Fe particles that cause deterioration of the magnetic properties, so the interval between the holes 7a is preferably 1.0 mm or more, more preferably 3.0 mm or more, and even more preferably 5.0 mm or more. From the viewpoints of the production efficiency of the rapidly solidified alloy and prevention of a decrease in the temperature at the nozzle tip, the interval between the holes 7a is preferably 20 mm or less. The shape of the opening of the nozzle 6 may be other shapes, such as a single hole.

[0047] The molten metal supplied to the surface of the chill roll 8 becomes a ribbon-shaped rapidly solidified alloy 9 by the rotation of the chill roll 8, and is peeled off from the chill roll 8. If the surface speed of the chill roll 8 is less than 15 m / sec, the rapidly solidified alloy becomes excessively thick, 40 μm or more, and the α-Fe crystal phase having an average crystal grain size of 100 nm or more and oriented in the (200) direction, which is precipitated by non-uniform nucleation during rapid solidification, may exceed 10.0 vol% near the surface of the chill roll surface or free surface of the iron-based soft magnetic alloy ribbon. On the other hand, if the surface speed of the chill roll 8 exceeds 50 m / sec, the thickness of the iron-based soft magnetic alloy ribbon becomes less than 18 μm, and the crushability of the rapidly solidified alloy ribbon is significantly reduced, so that in either case, it becomes difficult to obtain the desired alloy powder in the subsequent process. For this reason, the surface speed of the chill roll 8 is 15 m / sec or more and 50 m / sec or less, preferably 20 m / sec or more and 45 m / sec or less, and more preferably 25 m / sec or more and 40 m / sec or less. This makes it possible to form a thin ribbon of rapidly solidified alloy having a desired rapidly solidified alloy structure with a thickness of 18 μm or more and less than 40 μm, and excellent crushability.

[0048] 1(a), if the distance d from the tip of the single-slit nozzle 6 to the surface of the chill roll 8 is too small, the quenched alloy may stick to the chill roll 8, making it difficult to continue stable quenching and solidification of the molten alloy 3, whereas if the distance is too large, a puddle may not be formed on the surface of the chill roll 8, making it difficult to rapidly solidify the molten alloy 3. For this reason, the distance d is 0.1 mm or more and 2.0 mm or less, preferably 0.1 mm or more and 1.5 mm or less, and more preferably 0.15 mm or more and 1.0 mm or less.

[0049] When the nozzle 6 is a strand nozzle, if the distance d from the tip of the nozzle 6 to the surface of the cooling roll 8 in Fig. 1(a) is too small or too large, the same problem as in the case of the single slit nozzle described above occurs. For this reason, when the nozzle 6 is a strand nozzle, the distance d is 0.5 mm or more and 30.0 mm or less, preferably 1.0 mm or more and 20.0 mm or less, and more preferably 2.0 mm or more and 10.0 mm or less.

[0050] In producing the ribbon-shaped rapidly solidified alloy 9, the adhesion of the molten alloy 3 to the outer surface of the chill roll 8 is important, but this adhesion of the molten alloy is largely dependent on the surface roughness of the chill roll 8. If the surface roughness of the chill roll 8 is too small, the molten alloy 3 will slip on the surface of the chill roll 8, making sufficient cooling difficult, whereas if the surface roughness of the chill roll 8 is too large, the quenched alloy may stick to the chill roll 8. For this reason, the arithmetic mean roughness (Ra) of the surface of the chill roll 8 is 0.01 μm or more and 0.6 μm or less, preferably 0.05 μm or more and 0.55 μm or less, and more preferably 0.1 μm or more and 0.5 μm or less.

[0051] The chill roll 8 is preferably made of a material whose main raw material is any one of pure copper, copper alloy, molybdenum (Mo) and tungsten (W), thereby providing excellent thermal conductivity and durability. The main raw material means that it accounts for 50% or more by weight. The surface of the chill roll 8 may be plated with chromium, nickel or an alloy of these, which increases the heat resistance and hardness of the surface of the chill roll 8 and suppresses melting and deterioration of the roll surface during rapid solidification.

[0052] The diameter of the chill roll 8 is, for example, 200 to 20,000 mm. The chill roll 8 does not necessarily need to be water-cooled if the continuous quenching and solidification time is short, such as 10 seconds or less, but if the continuous quenching and solidification time exceeds 10 seconds, it is preferable to suppress a temperature rise on the surface of the chill roll 8 by running cooling water inside the chill roll 8. It is preferable to appropriately adjust the water-cooling capacity of the chill roll 8 according to the latent heat of solidification and the molten metal tapping rate per unit time.

[0053] [Crush] As described above, the manufacturing method of the iron-based soft magnetic alloy of the present invention can include a pulverization step of pulverizing the obtained iron-based soft magnetic alloy. As for the pulverization method, various pulverization devices such as a ball mill, a feather mill, a pin disk mill, and a jet mill are appropriately selected according to the molding method of the dust core. For example, in the case of general compression molding using a thermosetting resin as a binder, a high magnetic powder packing rate can be obtained by pulverizing to an average powder particle size of 70 μm to 200 μm using a feather mill and a pin disk mill. The average powder particle size is preferably 100 μm to 180 μm, and more preferably 100 μm to 140 μm. On the other hand, in injection molding, since a thermoplastic resin is generally used as a binder, a high magnetic powder packing rate can be obtained by pulverizing to an average powder particle size of 10 μm to 100 μm using a pin disk mill or a jet mill. In this case, the average powder particle size is preferably 20 μm to 80 μm, and more preferably 30 μm to 70 μm.

[0054] The tap density of the iron-based soft magnetic alloy powder obtained by the pulverization process is 2 g / cm 3 The tap density is measured in accordance with "Metal powder - Tap density measurement method" specified in JIS Z 2512:2012. The upper limit of the tap density is not particularly limited, but a tap density of 6 g / cm3 is preferable. 3 If the powder exceeds 6 g / cm3, the flowability of the powder in the cavity of the press die is significantly reduced in the case of compression molding, and a high molding density cannot be obtained. 3 The following is preferred:

[0055] [Heat treatment] The manufacturing method of the iron-based soft magnetic alloy of the present invention may further include a heat treatment step of heat treating the obtained iron-based soft magnetic alloy powder at a constant temperature of 180°C or more and 450°C or less. This makes it possible to remove distortion caused in the iron-based soft magnetic alloy powder due to the stress during pulverization, and is expected to have the effect of improving the iron loss and magnetic permeability of the iron-based soft magnetic alloy powder. As the heat treatment method, various heat treatment furnaces such as a batch furnace and a hoop belt furnace can be used, and a known method in which distortion removal heat treatment is completed in a short time of several seconds to several tens of seconds without increasing the heat capacity of the powder due to contact (accumulation) between the pulverized powders can be mentioned (for example, see Patent No. 6857392). The heat treatment temperature is preferably 200°C or more and less than 400°C, more preferably 200°C or more and less than 350°C. In addition, the above heat treatment is preferably performed in a vacuum or inert gas atmosphere, but heat treatment in the air is also acceptable as long as it is less than 350°C.

[0056] [Example] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the following examples.

[0057] 100 kg of raw materials containing B, C, Co and Fe with a purity of 99.5% or more were placed in an alumina crucible (melting furnace) and melted by high-frequency induction heating to form a molten alloy, so as to obtain the alloy compositions shown in Examples 1-9 and Comparative Examples 10-16 in Table 1 below. 50 kg of this molten alloy was poured into an alumina hot water storage container with an inner diameter of 200 mm and a height of 400 mm and equipped with a BN slit nozzle (Examples 1-4, 7-9, Comparative Examples 10-12 and Comparative Examples 14, 15) or a strand nozzle (Examples 5-6, Comparative Examples 13, 16) at the bottom. The slit width and length of the slit nozzle, or the diameter, hole interval and number of holes of the strand nozzle are as shown in Table 1.

[0058] Then, the 50 kg of molten alloy was further heated by passing electricity through a high-frequency heating coil installed around the molten alloy storage vessel. After the temperature of the molten alloy reached a temperature approximately 100°C higher than the melting point of the alloy composition, the alumina molten alloy stopper placed on the top of the nozzle was pulled out, and the molten alloy was sprayed from the nozzle onto the surface of the chill roll directly below. The chill roll was made of chrome zirconium copper, with an outer diameter of 600 mm and a width of 200 mm. The gap between the nozzle and the chill roll surface is as shown in Table 1. The spray pressure of the molten alloy from the nozzle, the roll surface speed of the chill roll, and the arithmetic mean roughness (Ra) of the roll surface of the chill roll are as shown in Table 2.

[0059] The molten alloy ejected onto the surface of the chill roll formed a puddle on the surface of the chill roll and was rapidly solidified at the interface between the puddle and the chill roll, producing a ribbon-shaped rapidly solidified alloy having the average thickness and average width shown in Table 3. When the structure of the obtained rapidly solidified alloy was evaluated by powder X-ray diffraction (XRD), it was found that all of the iron-based soft magnetic alloys of Examples 1-9 had a metal structure in which the α-Fe phase precipitated isotropically without being oriented in a specific direction.

[0060] As representative examples, the X-ray diffraction profiles of the iron-based soft magnetic alloy powders of Examples 2 and 7 are shown in Figures 2 and 3, respectively. In both Figures 2 and 3, the main α-Fe peak (110) and the secondary peak (200) diffraction peaks were confirmed, and both had wide half-widths, confirming that the fine metal structure was made of an isotropically precipitated α-Fe crystal phase. Also, a transmission electron microscope (TEM) photograph of Example 2 is shown in Figure 16. The metal structure of Example 2 shown in Figure 16 was an extremely fine metal structure made of α-Fe crystal precursors of 1 nm or less.

[0061] The saturation magnetic flux density Bs, the core loss (core loss) and magnetic permeability (μ) at a magnetic flux density of 1.0 T at 1 kHz, and the core loss at a magnetic flux density of 1.5 T at 20 kHz of the rapidly solidified alloys before pulverization obtained in Examples 1-9 are shown in Table 4. Measurement of Bs was performed using a vibration type sample magnetometer manufactured by Toei Kogyo Co., Ltd. Measurement of magnetic permeability μ and core loss was performed using an Iwasaki Electric Co., Ltd. BH analyzer equipped with an SST unit (single sheet magnetic property tester).

[0062] Next, the rapidly solidified alloys obtained in Examples 1-9 were coarsely pulverized to a few mm or less using a feather mill, and then finely pulverized using a pin disk mill. The average pulverized powder particle size (D50), tap density, and Bs after fine pulverization are shown in Table 5. The particle size distributions of the pulverized powders for Examples 2 and 7 are shown in Figures 4 and 5, respectively. The magnetization curves of the pulverized powders for Examples 2 and 7 are shown in Figures 6 and 7, respectively.

[0063] In addition, the pulverized powders obtained in Examples 6 and 7 were heat-treated at 260°C for 15 seconds in the same manner as the heat treatment method described in the above-mentioned Japanese Patent No. 6857392, respectively, to obtain heat-treated pulverized powders of Examples 8 and 9. A comparison of the magnetization curves of the pulverized powders of Examples 7 and 9 is shown in Figure 8. As shown in Figure 8, by performing heat treatment, the strain imparted to the rapidly solidified alloy by pulverization is alleviated, improving the magnetic permeability μ that was reduced by pulverization, and the rise of the initial magnetization curve becomes faster. In addition, it can be seen that the magnetization for each applied magnetic field is improved overall.

[0064] In addition, in Example 2, 2% by mass of thermosetting epoxy resin was added to the obtained iron-based soft magnetic alloy powder and kneaded to prepare a compound for compression molding, and then the powder was subjected to a compression pressure of 12 ton / cm. 2A toroidal ring with an outer diameter of 37 mm, an inner diameter of 17 mm, and a height of 6 mm was produced using a molding pressure of 10 ...

[0065] On the other hand, Comparative Example 10, 13 The Fe-Si-B rapidly solidified alloy of Comparative Example 12 was found to be dominated by an amorphous phase by powder X-ray diffraction (XRD) analysis. 11 In Comparative Example 15, the α-Fe phase was isotropically precipitated without being oriented in a specific direction, as in Examples 1-9. Comparative Example 14 had a structure consisting of an α-Fe phase, and Comparative Example 16 had a structure in which the α-Fe phase and amorphous matter were mixed. However, in Comparative Example 14, the peak intensity of α-Fe (200) was higher than that of α-Fe (110) by XRD, and it was found that α-Fe was oriented in-plane perpendicular to the thickness direction of the rapidly solidified alloy ribbon. In Comparative Example 15, the surface speed of the cooling roll was slow, so that the molten metal was not sufficiently quenched on the cooling roll, and the surface of the rapidly solidified alloy was oxidized, resulting in an alloy consisting of α-Fe and iron-based oxides. As representative examples, the powder X-ray diffraction profiles of the rapidly solidified alloy ribbons of Comparative Example 10 and Comparative Example 12 are shown in Figures 10 and 11. As shown in Figures 10 and 11, Comparative Example 10 had an amorphous single-phase structure, and Comparative Example 12 had a single-phase structure of α-Fe.

[0066] As in Examples 1-9, the saturation magnetic flux density Bs, the core loss (core loss) and magnetic permeability (μ) at a magnetic flux density of 1.0 T at 1 kHz, and the core loss at a magnetic flux density of 1.5 T at 20 kHz were measured for the rapidly solidified alloys obtained for Comparative Examples 10-16 before pulverization, and the results are shown in Table 4. Measurement of Bs was performed using a vibration type sample magnetometer manufactured by Toei Kogyo Co., Ltd. Measurement of magnetic permeability μ and core loss was performed using an Iwasaki Electric Co., Ltd. BH analyzer equipped with an SST unit (single sheet magnetic property tester).

[0067] Next, the rapidly solidified alloys obtained in Comparative Examples 10-16 were coarsely pulverized to a few mm or less using a feather mill, and then finely pulverized using a pin disk mill. The average pulverized powder particle size (D50), tap density, and Bs after fine pulverization are shown in Table 5. The powder particle size distribution of the Fe-Si-B amorphous rapidly solidified alloy powder obtained in Comparative Example 10 is shown in FIG. 12, and the magnetization curve is shown in FIG. 13. The powder particle size distribution of the (Fe,Co)-Si-B rapidly solidified alloy powder obtained in Comparative Example 12 is shown in FIG. 14. Comparative Example 12, which has a high concentration of Si and B, has an α-Fe precursor structure like Examples 1-9, but contains 30% or more of coarse powder of 250 μm or more even after fine pulverization using a pin disk mill, just like Comparative Example 10, which has an amorphous structure, and it can be seen that the pulverization is extremely poor. Also, in Comparative Example 14, the structure consisting of the α-Fe phase is coarsened, and the iron loss is significantly increased. In Comparative Example 16, the grinding was significantly reduced due to the inclusion of an amorphous phase, but in Comparative Example 15, iron-based oxides were formed in the surface layer of the rapidly solidified alloy, so grinding with a pin mill was abandoned.

[0068] For Comparative Example 10, a toroidal ring was produced from the obtained iron-based soft magnetic alloy powder, heat-cured, and insulated, and then the soft magnetic properties were evaluated, in the same manner as in Example 2. Fig. 15 shows the iron loss curve of the magnetic flux density and iron loss at 20 kHz in a toroidal ring-shaped dust core.

[0069] [Table 1]

[0070] [Table 2]

[0071] [Table 3]

[0072] [Table 4]

[0073] [Table 5] [Explanation of symbols]

[0074] l Single roll molten metal quenching device 2 Melting furnace 3 Molten alloy 4 Tilt axis 5. Hot water container 6. Water outlet nozzle 7 Slit 8. Cooling roll 9 Rapidly solidified alloys

Claims

1. Composition formula (Fe 1-m Co m ) 100-x-y S x (B 1-n C n ) y where the composition ratios x, y, m, and n are expressed as follows: 0.8≦x≦1.4 atomic%, 11.0≦y≦13.0 atomic%, 0.05≦m≦0.5、 0.0≦n≦0.3 preparing a molten alloy having a composition that satisfies the above; and a rapid solidification step of rapidly solidifying the molten alloy on a cooling roll made of any one of pure copper, copper alloy, Mo, and W as a main raw material, the rapid solidification step includes a step of spraying the molten alloy from a nozzle onto a surface of the chill roll while rotating the chill roll at a roll surface speed of 20 m / sec or more and 45 m / sec or less, thereby forming a ribbon-like rapidly solidified alloy having a thickness of 18 μm or more and less than 40 μm; The ribbon-shaped rapidly solidified alloy has a metal structure mainly composed of an α-Fe phase, a saturation magnetic flux density of 1.7 T or more and 2.0 T or less, and an iron loss of 15 W / kg or less at a magnetic flux density of 1.0 T and a frequency of 1 kHz, The surface roughness of the cooling roll is an arithmetic average roughness (Ra) of 0.01 μm or more and 0.6 μm or less, A method for producing an iron-based soft magnetic alloy, wherein the nozzle is made of a material whose main component is one of quartz (SiO2), boron nitride (BN), silicon carbide (SiC) and alumina (Al2O3), and the molten alloy is poured at a pressure of 5 kPa or more and 50 kPa or less.

2. the nozzle is a single slit nozzle, and is arranged so that a longitudinal direction of the slit is perpendicular to a rotation direction of the cooling roll; The opening width of the slit is 0.2 mm or more and 0.8 mm or less, 2. The method for producing an iron-based soft magnetic alloy according to claim 1, wherein the distance from the nozzle to the chill roll is 0.1 mm or more and 2.0 mm or less.

3. the nozzle is a strand nozzle having a plurality of holes arranged in a row perpendicular to the rotation direction of the cooling roll, The diameter of the hole is 0.6 mm or more and 1.3 mm or less, 2. The method for producing an iron-based soft magnetic alloy according to claim 1, wherein the distance from the nozzle to the chill roll is 0.5 mm or more and 30.0 mm or less.

4. 2. The method for producing an iron-based soft magnetic alloy according to claim 1, further comprising a pulverization step of pulverizing the ribbon-shaped rapidly solidified alloy to an average powder particle size of 200 μm or less to form an iron-based soft magnetic alloy powder.

5. The method for producing an iron-based soft magnetic alloy according to claim 4, further comprising a heat treatment step of heat treating the iron-based soft magnetic alloy powder at a constant temperature of 180°C or more and 450°C or less.

6. The iron-based soft magnetic alloy powder has a tap density of 2 g / cm 3 The method for producing an iron-based soft magnetic alloy according to claim 4,

7. 5. The method for producing an iron-based soft magnetic alloy according to claim 4, wherein the iron-based soft magnetic alloy powder has a residual magnetic flux density Bs of 1.5 T or more.

Citation Information

Patent Citations

  • Production of metal strip and nozzle for production

    JP1988220950A

  • Production of thin strip of amorphous alloy having large thickness

    JP1993329587A

  • Ferrous amorphous alloy

    JP1995113151A

  • Multilayered magnetic alloy thin strap

    JP1996124731A

  • METHOD FOR PRODUCING Fe-Si-B BASED RAPID-SOLIDIFIED ALLOY THIN STRIP

    JP2018153828A

Cited By

  • Iron-based soft magnetic alloy and its manufacturing method

    JP7765140B1